\(x-y+2xy=3\)
\(\Rightarrow2x-2y+4xy=6\)
\(\Rightarrow2x-2y+4xy-1=5\)
\(\Rightarrow\left(2x+4xy\right)-\left(2y+1\right)=5\)
\(\Rightarrow2x\left(2y+1\right)-1\left(2y+1\right)=5\)
\(\Rightarrow\left(2x-1\right)\left(2y+1\right)=5\)
\(x-y+2xy=3\)
\(\Leftrightarrow2\left(x-y+2xy\right)=2\times3\)
\(\Leftrightarrow2x-2y+4xy=6\)
\(\Leftrightarrow2x-2y+4xy-1=5\)
\(\Leftrightarrow\left(2x-4xy\right)-\left(2y+1\right)=5\)
\(\Leftrightarrow2x\left(2y+1\right)-\left(2y+1\right)=5\)
\(\Leftrightarrow\left(2x-1\right)\left(2y+1\right)=5\)
Bạn tự lập bảng để tìm nghiệm nhé